Factors related to non-adherence to the consumption of sparkling multimicronutrients in mothers of children aged 6 to 36 months - Lazarte y Avalos, Ana Gardenia (2018)
Objective. To identify the factors related to the non-adherence of the consumption of multimicronutrients (MMN) sprinkles in mothers of children from 6 to 36 months, users of the Carlos Showing Ferrari Health Center, Amarilis in Huánuco. Methods. It was a cross-sectional, analytical, and observational study. The population was 101 mothers, the selected sample was 41 mothers of children from 6 to 36 months; to whom an interview guide was applied, a questionnaire of the adherence of the consumption of MNN; and the factors of non-adherence; these instruments were valid and reliable. The non-parametric chisquare test was applied, with OR and a p <0.05. Results. When analyzing the adherence to the consumption of sparkling MNN, only 48% (20) of the sample were adherents. In social factors, non-dedication exclusively to the care of your child, in attitudinal factors "if the child had a respiratory disease or another disease, stop giving the spark"; on the factors related to the characteristics of NNM sparkles "when your child takes the sparkles, it causes constipation and diarrhea, or some other discomfort", also the fact that "when your child takes the sparkles, he has nausea" and the Cognitive factors, “ignorance of the content of sparkling MNN”, were related to non-adherence to the consumption of sparkling MNN. Conclusion. The cognitive and social factors were related to the non-adherence of the consumption of MNN.